KEBIJAKAN INDONESIA MERATIFIKASI PERJANJIAN KERJASAMA EKSTRADISI DENGAN PAPUA NUGINI 2015 - M. Fauzie Putra Sy; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The aim of this study is to understand extradition treaty between Indonesia and Papua New Guinea in handling transnational crime, factors affecting Indonesia’s policy in ratifying extradition treaty with Papua New Guinea, and also the impact of this agreement on Indonesia’s objectives regarding to transnational crime. One of the factors that influence the Indonesia’s foreign policy in ratifying extradition treaty with Papua New Guinea is the consideration of domestic political situation in the form of national security and economic interests. Therefore, it can be concluded that Indonesia’s policy in ratifying extradition treaty with Papua New Guinea that resulted in regulation No. 6 of 2015 concerning extradition is a form of security and economic interest for Indonesia. By ratifying the extradition treaty with Papua New Guinea, Indonesia is able to repatriate fugitive who fled to Papua New Guinea and resolve the transnational crime problem which involve two countries.Keywords: Extradition, Transnational Crime, National Interest